ALAT UKUR KADAR PATI PADA UBI KAYU BERBASIS SMS - Anggi Wahyudi; Nurmaya Sagita; Indra Dwisaputra; Aan Febriansyah (Politeknik Manufaktur Negeri Bangka Belitung, 2021)
In the industrial technology of cassava processing in Bangka Belitung, for now the level of productivity and efficiency of its performance can be said to be still minimal. This is because there is no supporting technology to measure the value of sweet potato starch levels digitally and efficiently. In this final project, a tool is designed to measure the starch content of cassava digitally based on SMS using the method specify gravity. The way this tool works is by measuring the mass of cassava in the air and in water using a driving medium in the form of a DC motor gearbox to raise and lower the cassava. Meanwhile, the sensor loadcell and HX711 are used for converting analog to digital data. The percentage of error obtained between the comparison of the weight value read on the sensor and the digital hanging scale is 0.282% and the result of the measuring instrument is able to measure starch content with a capacity of with an error of 2.45%. The measurement data can be sent via the SMS feature using the SIM800L V2 module with an average delivery speed of 7.12 seconds.